Disservice to Children; Advertising an Ethical issue - Khan, Sameer Mohammed (2007)
This study is conducted to expose the evidence about the effects of food advertising on children in Karachi, Pakistan. Advertising in itself is a powerfully suasive medium. Does food advertising leads to over weight and obese children? If it does than it raises questions about certain other serious health issues. What are the other supporting elements besides advertising leading to obesity? A small scale qualitative study was performed on school children and their parents to gather crucial information about the phenomenon. Results show that along with other elements of the society advertising is having and affect on children's eating and consumption behaviour and other activities.